Reduction in mitochondrial DNA methylation leads to compensatory increase in mitochondrial DNA content: novel blood-borne biomarkers for monitoring occupational noise - Jia-Hao Yang; Zhuo-Ran Li; Zhuo-Zhang Tan; Wu-Zhong Liu; Qiang Hou; Pin Sun; Xue-Tao Zhang (Environmental Health and Preventive Medicine)
Background: Prolonged occupational noise exposure poses potential health risks, but its impact on mitochondrial DNA (mtDNA) damage and methylation patterns remains unclear. Method: We recruited 306 factory workers, using average binaural high-frequency hearing thresholds from pure-tone audiometry to assess noise exposure. MtDNA damage was evaluated through mitochondrial DNA copy number (mtDNAcn) and lesion rate, and mtDNA methylation changes were identified via pyrophosphate sequencing. Results: There was a reduction in MT-RNR1 methylation of 4.52% (95% CI: −7.43% to −1.62%) among workers with abnormal hearing, whereas changes in the D-loop region were not statistically significant (β = −2.06%, 95% CI: −4.44% to 0.31%). MtDNAcn showed a negative association with MT-RNR1 methylation (β = −0.95, 95% CI: −1.23 to −0.66), while no significant link was found with D-loop methylation (β = −0.05, 95% CI: −0.58 to 0.48). Mediation analysis indicated a significant increase in mtDNAcn by 10.75 units (95% CI: 3.00 to 21.26) in those with abnormal hearing, with MT-RNR1 methylation mediating 35.9% of this effect. Conclusions: These findings suggest that occupational noise exposure may influence compensatory increases in mtDNA content through altered MT-RNR1 methylation.